The Influence of Fashion Retailers on Customer Psychology Using Visual Merchandising and Store Layout to Improve Shopping Decision - Nicoleta-Valentina Florea; Gabriel Croitoru; Dan-Marius Coman; Mihaela-Denisa Coman (Journal of Theoretical and Applied Electronic Commerce Research)
This study explores how visual merchandising and store layout influence customer shopping decisions. This research aims to identify the key factors that shape consumer behavior and provide useful insights for retailers by using interactive marketing factors. Data were collected from 488 respondents in the South Muntenia region of Romania, a key economic hub with significant retail activity. Given its economic diversity and proximity to Bucharest, this region serves as a representative microcosm of consumer behavior trends in Romania. The survey was distributed physically and virtually through social media platforms (Facebook and WhatsApp groups, and email networks) to ensure a diverse and representative sample. To analyze the data, this study utilized SmartPLS, a powerful tool for structural equation modeling (SEM). This approach allowed for an in-depth examination of the relationships between visual merchandising, store layout, and customer shopping behavior, providing a more comprehensive view of the conceptual model. This study’s theoretical contributions stem from its holistic approach, which combines different aspects of visual merchandising and store layout into a unified conceptual model. By analyzing how these elements work together, this study offers a deeper understanding of customer shopping behavior. Retailers are encouraged to prioritize product arrangement, make effective use of exterior lighting, and maintain engaging window displays. These strategies can attract more customers, encourage impulse purchases, and improve the overall store profitability. This study underscores the critical role that visual merchandising and store layout play in shaping customer shopping decisions. By optimizing product layout, enhancing exterior lighting, and creating captivating window displays, retailers can design a more engaging shopping experience that boosts customer satisfaction, increases sales, and builds customer loyalty.